Characteristics of Sengon Rotary-Cut Veneer - Abigael Kabe; Wayan Darmawan; Muhammad Y Massijaya (Masyarakat Peneliti Kayu Indonesia, 2012)
Fast growing sengon is largely rotary-cut to produce veneer for plywood, com-ply and LVL. In order to provide better information on veneer production and utilization, in this study the effects of wood juvenility and veneer thickness on lathe checks of sengon rotary-cut veneer were evaluated. Before veneer manufacturing, the sengon log was boiled at 50 and 75 oC for 4 and 8 h, respectively. The boiled logs were peeled to produce veneer of 1 and 2 mm in thickness. Lathe checks of veneers were measured under an optical video microscope. The rotary-cut veneer was grouped and evaluated separately at every segmented ring of 2 cm from pith to bark. The results showed that wood juvenility and veneer thickness had an important effect on lathe checks for the rotary-cut veneer. In general, the number of lathe check of the veneer increases with increasing veneer thickness and increase from pith to bark. Boiling of logs before rotary-cutting could decrease the value of lathe check. The results indicated that boiling of logs at 50 oC for 8 h, and at 75 oC for 4 and 8 h could minimize the number of lathe checks in manufacturing of 1 and 2 mm rotary-cut veneer from juvenile wood sengon.Key words: juvenility, lathe check, Paraserianthes falcataria, rotary-cut veneer, veneer thickness